Effects of Socio-Cultural Behaviour on Covid-19 Protocol among Rural Dwellers in Rivers State, Nigeria - Adegbite, Stella N.; Ijah, Christiana N. (NIU Journal of Humanities; Vol 8 No 1 (2023): NIU Journal of Humanities, Vol. 8 No. 1, March 2023DO - 10.58709/niujhu.v8i1.1579, 2023)
This study examines the effects of socio-cultural behaviour on Covid-19 protocol among rural dwellers in Rivers State, Nigeria. The study is a guided by two research questions and research design is the descriptive survey research design. The population of the study was drawn from members of community-based organisations in five rural communities in Emohua Local Government Area of Rivers State, Nigeria. The purposive and convenient sampling techniques were adopted using 400 members of the CBOs. The instrument used for data collection is a self-structured questionnaire titled- “Assessment of effects of socio-cultural behaviour of rural dwellers in the prevention and spread of covid-19 Questionnaire (AESCBRDPSCQ)”. The questionnaire is complimented by the use of observation in data collection.  The instrument was validated using face and content validity and the reliability of the instrument was determined using the test-retest method. The descriptive statistics mean and percentage were used to analyze the data collected. The study reveals that the socio-cultural behaviours such as the religious rites, festivals, pattern of greeting and funeral rites and festivals undermine the observation of the Covid-19 protocols. The study also reveals that there were innovative socio-cultural behaviours such as the drinking of herbal drinks to boost immunity, and the use of local made face mask from local fabrics. The study concludes that some socio-cultural behaviours of the people in rural communities tends to prevent the spread of Covid-19 and that such ingenious innovative actions of the rural communities in times of pandemic should be encouraged and integrated into the national health system.